A modal-based approach for modelling the cantilever FBG accelerometer with the presence of tip mass and its sensitivity analysis - Nor Syukriah, Khlaid; Mohd Firdaus, Hassan; Rahim, Muhammad Rais (Elsevier, 2022)
The modal-based approach for modelling cantilever-type FBG accelerometer (FBG-MM), which has been recently published, does not include the presence of tip mass and sensitivity study since it mainly focusses on the feasibility of the Euler-Bernoulli model onto a cantilever FBG accelerometer. The adaptability of tip mass into the modal model of the cantilever FBG accelerometer, namely FBG-MMTP, is presented in this manuscript, which can precisely predict the response and sensitivity of the accelerometer. The newly presented model is compared to the experimental results for different sizes of tip mass and the range of excitation frequencies less than its resonant frequency. Within the transmission range, there is an excellent agreement between the time response of wavelength shift calculated using FBG-MMTP and the experimental results. The sensitivity obtained from both FBG-MMTP and experimental results is roughly comparable, with around 25% discrepancies, which are thought to be due to imprecision in the physical dimension of tip mass and beam, as well as measurement errors.